THE INFLUENCE OF JOB SATISFACTION, WORK MOTIVATION, AND EMPLOYEE COMMITMENT ON EMPLOYEE PERFORMANCE - Michael Sanjaya; Lilik Indrawati (Research In Management and Accounting (RIMA), 2023)
Every organization carries out various activities to achieve predetermined goals, but in achieving these goals it often experiences obstacles because the employees they have do not have maximum performance. This research was conducted to determine the effect of job satisfaction, work motivation, and employee commitment on employee performance. The contribution of this research is expected to be able to add information at the theoretical or scientific level of human resource management and also have implications for human resource management in companies. The study used the survey method as a data collection technique, and a questionnaire as an instrument and was distributed to a sample of 138 employees. The data analysis technique used was multiple linear regression and the data processing method used SPSS version 25. The results showed that job satisfaction has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, and employee commitment has a positive and significant effect on employee performance. For this reason, the importance of PT Salam Pacific Indonesia Lines company management in an effort to improve employee performance needs to pay attention to the factors of job satisfaction, work motivation, and employee commitment.